Autoimmune-mediated astrocytopathy - Makoto Kinoshita; Tatsusada Okuno (BMC, 2023)
Abstract Recently accumulating evidence identified the disease entity where astrocytes residing within the central nervous system (CNS) are the target of autoantibody-mediated autoimmunity. Aquaporin4 (AQP4) is the most common antigen to serve as astrocyte-targeted autoimmune responses. Here, in this review, the clinical and pathological aspects of AQP4-mediated astrocyte disease are discussed together with the pathogenic role of anti-AQP4 antibody. More recently, the mechanism of immune dysregulation resulting in the production of astrocyte-targeted autoantibody is also revealed, and the postulated hypothesis is discussed.